2022
DOI: 10.3390/healthcare10081440
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medications among Elderly with Frailty in a Tertiary Care Academic Medical Centre in Saudi Arabia

Abstract: This study aims to assess the prevalence of potentially inappropriate medications (PIMs) and to analyze the relationship between the PIMs and frailty among inpatient older adults aged 65 and above in Saudi Arabia. A retrospective cross-sectional study design was utilized during the period between April 2021 and April 2022 of all patients aged 65 years and above admitted in a public tertiary hospital in Saudi Arabia. Data on the number of medications and the use of PIMs were assessed using Beers’ criteria while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Consequently, the final number of studies included in this systematic review amounted to 8, as indicated in Figure 2. (Al-Omar et al, 2013;Jastaniah et al, 2018;Alhawassi et al, 2019;Alturki et al, 2020;Alsaad et al, 2022;Alwhaibi, 2022;Alharbi et al, 2022;Jabri et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, the final number of studies included in this systematic review amounted to 8, as indicated in Figure 2. (Al-Omar et al, 2013;Jastaniah et al, 2018;Alhawassi et al, 2019;Alturki et al, 2020;Alsaad et al, 2022;Alwhaibi, 2022;Alharbi et al, 2022;Jabri et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the need for further research efforts to explore such phenomena in more depth. Additionally, it is noteworthy that 6 out of the included studies (constituting 75%) (Al-Omar et al, 2013;Alhawassi et al, 2019;Alturki et al, 2020;Alsaad et al, 2022;Alwhaibi, 2022;Jabri et al, 2023) focused on the elderly population, typically defined as individuals aged 65 years or older the standard definition of elderly in the US or United Kingdom studies. The two remaining studies (Alharbi et al, 2022;Jastaniah et al, 2018) considered a broader age category of 60 years or older, a specification more relevant to the region due to economic, life expectancy, retirement age, and health-related distinctions between the Saudi population and older adult populations in the United Kingdom or US.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations